Characteristics of activated carbon from coconut shell (Cocos nucifera) through chemical activation process. Issue 1 (April 2021) - Lutfi, M; Hanafi,; Susilo, B; Prasetyo, J; Sandra,; Prajogo, U
Abstract: Activated carbon is a material that widely used in industries as an adsorbent and purifying material. Moreover, activated carbon has an essential role in improving product quality. Coconut shell has many advantages to be used as activated carbon sources as it has both high mechanical strength and high pore volume. This research aims to explore the coconut shell as an activated carbon material through immersion using a phosphoric acid solution. The activation process was conducted under different conditions, i.e. H PO concentration of 1 M, 2 M, 3 M, 4 M and 5 M, and immersion time of 1 hour, 3 hours, 5 hours, 7 hours and 9 hours. The characteristics of the activated carbon were evaluated in terms of iodine number, density, water content and ash content. It could be concluded that the combination of 3M H PO concentration and 9 hours immersion time was the best combination for producing desirable activated carbon from coconut shell. The characteristics of iodine number, density, water content and ash content are 248.5811 mg/g, 1.3613 g/ml, 5.3628% and 2.1239%, respectively. The phosphate acid concentration and the immersion time had a significant effect on the activated carbon characteristics such as iodine number, density, water content and ash content.